ASSESSMENT OF WASTE MANAGEMENT PRACTICES AND THEIR IMPACT ON COMMUNITY HEALTH IN IBADAN NORTH LGA - Adebayo, Francisca Chinyere; familoni, idowu .I (PhD); Adegbenjo , Adebola Monsurat; Shofolahan, Paulina Olubunmi (African Journal of Behavioural and Scale Development Research, 2025)
ABSTRACT Effective waste management is essential for protecting community health and maintaining environmental quality. Poor waste management practices can lead to serious public health issues and environmental degradation, making it crucial to understand and address these challenges. This study investigates waste management practices in Ibadan North Local Government Area (LGA) and their impact on community health to inform better strategies for waste management and public health interventions. The study involved 384 who provided data through structured questionnaires. SPSS software was utilized for data analysis, employing frequency percentages and chi-square tests to examine waste management practices and their health impacts. Results indicated that 54.9% of had good waste management practices, while 45.1% had poor practices. Major challenges identified included inadequate waste collection services (81.8% dissatisfaction), lack of proper disposal facilities (77.0%), and insufficient public education (65.6%). The frequency of waste collection services was predominantly monthly (59.0%), and common disposal methods included open dumping (29.7%) and private waste management services (25.0%). Health impacts were significantly associated with waste management practices. A higher prevalence of typhoid (61.1%, p < 0.001), skin diseases (61.5%, p < 0.001), and gastrointestinal infections (52.9%, p = 0.037) was observed among those with poor waste management practices. However, no significant associations were found for cholera (p = 0.599), respiratory infections (p = 0.844), or malaria (p = 0.059). In conclusion, the study underscores the need for improved waste management practices to reduce health risks. Important first steps towards improved community health are strengthening waste collecting programs, public education, and waste management rules enforcement. Keywords: Waste Management, Community Health, Public Health, Typhoid, Waste Disposal Practices Word count: 264